Market analysis based on product of i) Talcom Powder, ii) Calsium Carbonate and iii) Dolomite powder - Hasan, Qazi Mahmudul (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration,2014.